Porrajmos - Cigány holokauszt - Varga, Ágota (Hungary : Profilm Média Kft., 2000)
The long-silenced and unprocessed story of the Gypsy Holocaust is brought to life by this shocking documentary through the recollections of survivors. Porrajmos commemorates the Roma taken to death camps and exterminated by the Nazis and Arrow Cross through the personal recollections of the survivors.
Yellow Star Houses Film Program 2014
Keywords: Documentary films